Strategi Branding Public Relations “Jendela Alam” dalam Mengembangkan Produk Agrowisata - Femi Oktaviani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
Public Relations has an important role and function in managing business activities. One of which is relied on to develop agro tourism products that can create a branding reinforcement of a product to the public. Performing a public relations strategy is done so that perception value can be well received by the public. This study aims to study the branding strategy of public relation of window Jendela Alam in developing agrotourism products that focus on building trust with stakeholders, conducting external activities and choosing the communication media. This study uses qualitative methods with a case study approach. Data collection techniques used are observation, interviews, and literature studies. The results show that building trust with various stakeholders is needed in strengthening the branding. This can be done with integrity, credibility and capability. External communication is carried out as a means for companies to establish and develop relationships with stakeholders, as well as the use of communication media to publish all forms of the Jendela Alam activities in developing agro-tourism products so that the public knows various information about agrotourism products while strengthening the Jendela Alam agrotourims products.